Statistics - Johnson Allan (Harcourt Brace Jovanovich, Publishers, 1988)
Description and Explanation, An Introduction to Statistics and the Problems of Knowing, Measurement, Distributions and Comparisons and Tables, Summarizing Distributions, Elementary Probability Theory, Relationships Between Two Variables: Nominal and Ordinal Scales, Relationships of More Than Two Variables: Controlling, Multivariate Analysis, Statistical Inference, Sampling, Estimating Population Means and Proportions, Hypothesis Testing.